Carbon quantum dot modified silicon-carbon negative electrode material as well as preparation method and application thereof
By introducing carbon quantum dots into the porous carbon substrate for modification, the problem of poor expansion and rate performance of silicon carbon materials in lithium-ion batteries is solved, and high capacity, high first-term efficiency and excellent electrochemical performance are achieved.
Patent Information
- Application Number
- CN202411926126.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-25
- Publication Date
- 2025-03-28
AI Technical Summary
Existing silicon carbon materials have problems with poor expansion and rate performance in lithium-ion batteries, mainly due to the selection and failure to effectively modify the porous carbon substrate, resulting in large silicon particles and uneven distribution.
Modify porous carbon by introducing carbon quantum dots to optimize its pore structure and mechanical properties, thereby improving overall conductivity and uniformity and miniaturization of silicon particles.
The excellent rate performance and cycle stability of silicon-carbon materials are achieved, as well as high capacity and high first-term efficiency, effectively constraining the volume expansion of silicon and improving electrochemical performance.
Smart Images

Figure CN119725465A_ABST
Abstract
Description
Technical Field
[0001] The present invention belongs to the technical field of lithium-ion batteries, and specifically relates to a carbon quantum dot-modified silicon-carbon negative electrode material, a preparation method and an application thereof. Background Art
[0002] With the development of electric vehicles and low-altitude economy, lithium-ion batteries have been widely used; however, due to the low energy density of graphite (372mAh / g), lithium batteries generally have a short driving range, making the improvement of electrochemical performance a key issue that needs to be urgently addressed in the development of lithium-ion battery technology. Compared with battery structure design, the research on high specific capacity active materials has shown greater advantages in improving energy density; silicon-based materials have gradually developed into the next generation of negative electrode materials with the most application prospects due to their high theoretical capacity (4200mAh / g), abundant resources, and low cost; although silicon negative electrodes have high specific capacity, their lithium storage process will form lithium-silicon alloys, causing large volume changes in materials and electrodes, and even causing particle pulverization, which seriously affects the application of silicon negative electrodes.
[0003] In view of the problems of silicon negative electrode materials themselves, and the fact that lithium-ion batteries need fast charging and discharging in many application scenarios, it is necessary to assemble and design the silicon material structure to effectively restrict the volume expansion of silicon and achieve performance improvement; the carbon material has a stable structure, and the volume change is relatively small during the charging and discharging process, has good cycle stability, and has similar chemical properties to silicon. Silicon and carbon are often compounded to achieve the purpose of improving the volume expansion effect of silicon and improving its electrochemical stability. However, the existing silicon carbon is compounded by silicon and a porous carbon substrate through vapor deposition, and the expansion and rate performance of the obtained negative electrode material are poor, making it difficult to use silicon carbon materials in lithium-ion batteries on a large scale. The main reason for this is the selection of porous carbon substrates; in the prior art, biomass-based or resin-based porous carbon is directly selected for silane deposition, and the porous carbon substrate is not well modified and modified; the proportion of effective pores in the porous carbon that can be perfectly used for silane deposition is low, the deposition and distribution of silicon atoms in the porous carbon are uneven, and the size of silicon particles in the porous carbon is large, which leads to poor expansion and rate performance of the negative electrode material. Therefore, it is very important to reduce the size of silicon particles in porous carbon, and the modification and pore size regulation of the porous carbon substrate are particularly critical.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] In view of the above problems, the present invention discloses a carbon quantum dot-modified silicon-carbon negative electrode material, a preparation method and its application. In the present invention, the introduction of carbon quantum dots improves the overall conductivity of the negative electrode material, optimizes the pore structure of the porous carbon substrate, and improves the mechanical properties of the porous carbon substrate. The battery assembled with the modified silicon-carbon negative electrode material has excellent rate performance and cycle stability, as well as high capacity and high initial efficiency.
[0006] To achieve the above purpose, the specific technical solution of the present invention is as follows:
[0007] In a first aspect, the present invention provides a carbon quantum dot-modified silicon-carbon negative electrode material, comprising a modified porous carbon substrate, nano-silicon deposited in the modified porous carbon substrate, and a carbon layer uniformly coated on the modified porous carbon substrate and / or the nano-silicon;
[0008] According to XRD test, the half peak width of the nano-silicon is not less than 2.5;
[0009] The half-width refers to the peak width of the silicon-carbon negative electrode material at half the peak height of the silicon diffraction peak at 28° in the XRD diagram. The half-width of the nano-silicon given in the present invention is related to the grain size and disorder degree of the nano-silicon. The larger the half-width, the smaller the grain size of the nano-silicon, the higher the disorder degree, and the relatively weaker the expansion.
[0010] Optionally, the half-peak width of the nano-silicon is not less than 3.5;
[0011] Further optionally, the half-peak width of the nano-silicon is not less than 4.0.
[0012] In an optional embodiment, the modified porous carbon substrate satisfies at least one of the following A to D:
[0013] A. Modification of porous carbon substrate D 50 =5~12μm;
[0014] B. The specific surface area of the modified porous carbon substrate is 1600-2400 m 2 / g;
[0015] C. The total pore volume of the modified porous carbon substrate is 0.70-1.20 cm 3 / g;
[0016] D. The average pore size of the modified porous carbon substrate is 1 to 5 nm.
[0017] In an optional embodiment, the modified porous carbon substrate is obtained by uniformly mixing porous carbon and a carbon quantum dot solution and then subjecting the mixture to a modification treatment.
[0018] In an optional embodiment, the carbon quantum dot-modified silicon-carbon negative electrode material satisfies at least one of the following A to F:
[0019] AD 50 8±1μm;
[0020] B. Tap density is 0.9±0.1g / cm 3 ;
[0021] C. Resistivity is 1~5Ω·cm;
[0022] D. Specific surface area is 1 to 3 m 2 / g;
[0023] E. The mass percentage of the carbon layer is 1 to 5 wt%;
[0024] F. The average size of nano-silicon is no more than 3.5nm.
[0025] In a second aspect, the present invention provides a method for preparing the above-mentioned carbon quantum dot-modified silicon-carbon negative electrode material, comprising:
[0026] Porous carbon modification, mixing the porous carbon and the carbon quantum dot solution evenly, transferring the mixture into a high-pressure reactor for modification treatment, and obtaining modified porous carbon;
[0027] Silicon deposition, placing the modified porous carbon as a substrate in a raw gas environment containing a silicon source gas, and performing vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles;
[0028] Carbon coating treatment is performed by placing a porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a silicon-carbon negative electrode material modified with carbon quantum dots.
[0029] The present invention uses a carbon quantum dot solution to modify porous carbon. Under optimized modification process and parameters, the electrical conductivity of the porous carbon material can be significantly improved, which helps to improve the overall conductivity of the composite material, thereby improving the rate performance of the silicon-carbon material; secondly, the pore structure of the porous carbon substrate can be further optimized to provide more active sites, so that the silicon particles are smaller and more uniform during the deposition of silicon atoms on the porous carbon substrate; finally, the mechanical properties of the porous carbon substrate can be improved, and the integrity and stability of its structure can be enhanced, which is of great help to the expansion performance of the silicon-carbon material.
[0030] In an optional embodiment, the porous carbon modification comprises at least one of the following features (1) to (7):
[0031] (1) The porous carbon is selected from one or more of biomass-based, resin-based, asphalt-based, and petroleum-based;
[0032] (2) Preparation of carbon quantum dot solution, specifically including:
[0033] Mixing raw material A, raw material B and water to obtain a mixed solution, and subjecting the mixed solution to microwave heating treatment;
[0034] (3) Raw material A includes but is not limited to one or more of citric acid, acetic acid, glucose, sucrose, and lactose;
[0035] Optionally, raw material A is selected from citric acid and glucose;
[0036] Raw material B includes but is not limited to one or more of urea, melamine, and dicyandiamide;
[0037] Optionally, raw material B is selected from urea;
[0038] (4) The mass ratio of raw material A to raw material B is 1:(1-5), and the concentration of raw material B in the mixed solution is 0.5-10.0 mol / L;
[0039] Optionally, the mass ratio of raw material A to raw material B is 1:(1-1.5);
[0040] Optionally, the concentration of raw material B in the mixed solution is 2 to 5 mol / L;
[0041] (5) Microwave heating treatment, power of 200-1000 W, temperature of 60-100° C., time of 5-60 min;
[0042] Optionally, microwave heating treatment with a power of 400 to 800 W;
[0043] Optionally, the microwave heating treatment is performed at a temperature of 70 to 90° C.; further optionally, the temperature is 80° C.;
[0044] Optionally, microwave heating treatment for 20 to 60 minutes;
[0045] (6) The mass ratio of the total mass of raw material A and raw material B to the mass of porous carbon is (1-5):(1-10);
[0046] Optionally, the mass ratio of the total mass of raw material A and raw material B to the mass of porous carbon is 1:(2-5);
[0047] Further optionally, the mass ratio of the total mass of raw material A and raw material B to the porous carbon is 1:(2-4); more optionally, the mass ratio is 1:(2-3);
[0048] (7) Modification treatment, pressure is 2-10 MPa, temperature is 150-200°C;
[0049] Optionally, the pressure of the modification treatment is 4 to 8 MPa;
[0050] Further optionally, the pressure of the modification treatment is 6 to 8 MPa.
[0051] In an optional embodiment, the carbon quantum dot solution is prepared by microwave heating and then secondary heating;
[0052] Experiments have shown that secondary heating can further enhance the bonding ability between carbon quantum dots and porous carbon, improve the quality of modified porous carbon, further improve the conductivity of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material, and the electrochemical properties of the final assembled battery, including rate performance and cycle stability.
[0053] Optionally, the secondary heating is performed at a temperature of 60 to 80° C.
[0054] Optionally, the secondary heating is performed for 1 to 5 hours.
[0055] In an optional embodiment, the crude product after microwave treatment, or microwave and secondary heating treatment, needs to be centrifuged multiple times until no sediment appears, and the centrifuged solution is collected as the carbon quantum dot solution;
[0056] Optionally, the centrifugal treatment has a rotation speed of 1500 to 3000 r / min.
[0057] In an alternative embodiment, the silicon deposition:
[0058] The raw material gas used includes silicon source gas;
[0059] Optionally, the silicon source gas includes but is not limited to common types such as silane and silicon tetrachloride.
[0060] The flow rate of the silicon source gas is 1 to 15 L / min;
[0061] The silicon deposition temperature is 400-580°C;
[0062] Optionally, the temperature of the silicon deposition is 420-520° C.;
[0063] Optionally, the silicon deposition is carried out in a rotary kiln; further optionally, the rotation speed of the rotary kiln is 0.1 to 2.5 r / min;
[0064] The silicon deposition time is 2 to 20 hours;
[0065] In an optional embodiment, the carbon coating process:
[0066] The raw gas used includes carbon-containing gas;
[0067] Optionally, the carbon-containing gas is selected from at least one of C1-4 alkanes, such as methane, ethane, propane, butane, C2-4 olefins, such as ethylene, propylene, butene, 1,3-butadiene, and C2-4 alkynes, such as acetylene, propyne, and butyne;
[0068] The flow rate of the carbon-containing gas is 1 to 15 L / min;
[0069] Optionally, the carbon coating treatment is also carried out in a rotary kiln; further optionally, the rotation speed of the rotary kiln is 0.1 to 2.5 r / min;
[0070] The carbon coating treatment is performed at a temperature of 500 to 1000°C;
[0071] Optionally, the temperature of the carbon coating treatment is 550-750°C;
[0072] The carbon coating process is performed under an inert atmosphere.
[0073] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned carbon quantum dot-modified silicon-carbon negative electrode material.
[0074] In a fourth aspect, the present invention further provides a secondary battery comprising the above-mentioned negative electrode material.
[0075] Compared with the prior art, the present invention has the following beneficial results:
[0076] The present invention discloses a silicon-carbon negative electrode material modified by carbon quantum dots and a preparation method thereof. The porous carbon substrate is modified by introducing carbon quantum dots. The introduction of carbon quantum dots can improve the conductivity of the porous carbon material, help to improve the overall conductivity of the composite material, and thus improve the rate performance of the silicon-carbon material. Secondly, the pore structure of the porous carbon substrate can be further optimized to provide more active sites, so that the silicon particles are smaller and more uniform during the deposition of silicon atoms on the porous carbon substrate. Finally, the mechanical properties of the porous carbon substrate can be improved, and the integrity and stability of its structure can be improved, which is of great help to the expansion performance of the silicon-carbon material.
[0077] The battery assembled with the silicon-carbon negative electrode material prepared by the present invention has excellent rate performance and cycle stability, as well as high capacity and high initial efficiency. BRIEF DESCRIPTION OF THE DRAWINGS
[0078] Figure 1 XRD diagrams of carbon quantum dot-modified silicon-carbon composite negative electrode materials prepared in Example 8 and Comparative Example 4, respectively. DETAILED DESCRIPTION
[0079] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0080] In the description of the present invention, it should be noted that, for those of ordinary skill in the art, the specific meanings of the above terms in the present invention can be understood in specific circumstances. Below, according to the overall structure of the present invention, its embodiments are described. Unless otherwise specified, the raw materials in the embodiments of the present invention are purchased through commercial channels.
[0081] In a first aspect, the present invention provides a carbon quantum dot-modified silicon-carbon negative electrode material, comprising a modified porous carbon substrate, nano-silicon deposited in the modified porous carbon substrate, and a carbon layer uniformly coated on the modified porous carbon substrate and / or the nano-silicon;
[0082] According to XRD test, the half-peak width of the nano-silicon is not less than 2.5; specifically, it can be not less than 2.5, 2.6, 2.7, 2.8, 2.9, 3.0, 3.2, 3.5, 3.7, 4.0, 4.3, 4.4, 5.0, 5.3 or any value within the above range.
[0083] The half-width refers to the peak width of the silicon-carbon negative electrode material at half the peak height of the silicon diffraction peak at 28° in the XRD diagram. The half-width of the nano-silicon given in the present invention is related to the grain size and disorder degree of the nano-silicon. The larger the half-width, the smaller the grain size of the nano-silicon, the higher the disorder degree, and the relatively weaker the expansion.
[0084] Optionally, the half-peak width of the nano-silicon is not less than 3.5;
[0085] Further optionally, the half-peak width of the nano-silicon is not less than 4.0.
[0086] In an optional embodiment, the modified porous carbon substrate satisfies at least one of the following A to D:
[0087] A. Modification of porous carbon substrate D 50 =5~12μm; specifically, it can be 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm or any value within the above range.
[0088] B. The specific surface area of the modified porous carbon substrate is 1600-2400 m 2 / g; specifically, 1600m 2 / g、1700m 2 / g、1800m 2 / g、1900m 2 / g, 2000m 2 / g, 2100m 2 / g, 2200m 2 / g, 2300m 2 / g, 2400m 2 / g or any value within the above range.
[0089] C. The total pore volume of the modified porous carbon substrate is 0.70-1.20 cm 3 / g; specifically, it can be 0.70cm 3 / g, 0.75cm 3 / g, 0.80cm 3 / g, 0.85cm 3 / g, 0.90cm 3 / g, 0.95cm 3 / g, 1.00cm 3 / g, 1.05cm 3 / g, 1.10cm 3 / g, 1.15cm 3 / g, 1.20cm 3 / g or any value within the above range.
[0090] D. The average pore diameter of the modified porous carbon substrate is 1 to 5 nm; specifically, it can be 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm, 4 nm, 4.5 nm, 5 nm or any value within the above range.
[0091] In an optional embodiment, the modified porous carbon substrate is obtained by uniformly mixing porous carbon and a carbon quantum dot solution and then subjecting the mixture to a modification treatment.
[0092] In an optional embodiment, the carbon quantum dot-modified silicon-carbon negative electrode material satisfies at least one of the following A to F:
[0093] AD 50 It is 8±1μm; specifically, it can be 7μm, 7.2μm, 7.4μm, 7.6μm, 7.8μm, 8μm, 8.2μm, 8.4μm, 8.6μm, 8.8μm, 9μm or any value within the above range.
[0094] B. Tap density is 0.9±0.1g / cm 3 ; Specifically, it can be 0.8g / cm 3 , 0.82g / cm 3 , 0.85g / cm 3 , 0.88g / cm 3 , 0.9g / cm 3 、0.92g / cm 3 , 0.95g / cm 3 、0.98g / cm 3 , 1.0g / cm3 Or any value within the above range.
[0095] C. The resistivity is 1 to 5Ω·cm; specifically, it can be 1Ω·cm, 1.5Ω·cm, 2Ω·cm, 2.5Ω·cm, 3Ω·cm, 3.5Ω·cm, 4Ω·cm, 4.5Ω·cm, 5Ω·cm or any value within the above range.
[0096] D. Specific surface area is 1 to 3 m 2 / g; specifically, it can be 1m 2 / g, 1.2m 2 / g, 1.5m 2 / g, 1.8m 2 / g, 2m 2 / g, 2.2m 2 / g, 2.5m 2 / g, 2.8m 2 / g, 3m 2 / g or any value within the above range.
[0097] E. The mass percentage of the carbon layer is 1 to 5wt%; specifically, it can be 1wt%, 1.5wt%, 2wt%, 2.5wt%, 3wt%, 3.5wt%, 4wt%, 4.5wt%, 5wt% or any value within the above range.
[0098] F. The average size of nano-silicon is not greater than 3.5 nm; specifically, it can be 0.1 nm, 0.5 nm, 1 nm, 1.5 nm, 2 nm, 2.5 nm, 3 nm, 3.5 nm or any value within the above range.
[0099] In a second aspect, the present invention provides a method for preparing the above-mentioned carbon quantum dot-modified silicon-carbon negative electrode material, comprising:
[0100] Porous carbon modification, mixing the porous carbon and the carbon quantum dot solution evenly, transferring the mixture into a high-pressure reactor for modification treatment, and obtaining modified porous carbon;
[0101] Silicon deposition, placing the modified porous carbon as a substrate in a raw gas environment containing a silicon source gas, and performing vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles;
[0102] Carbon coating treatment is performed by placing a porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a silicon-carbon negative electrode material modified with carbon quantum dots.
[0103] The present invention uses a carbon quantum dot solution to modify porous carbon. Under optimized modification process and parameters, the electrical conductivity of the porous carbon material can be significantly improved, which helps to improve the overall conductivity of the composite material, thereby improving the rate performance of the silicon-carbon material; secondly, the pore structure of the porous carbon substrate can be further optimized to provide more active sites, so that the silicon particles are smaller and more uniform during the deposition of silicon atoms on the porous carbon substrate; finally, the mechanical properties of the porous carbon substrate can be improved, and the integrity and stability of its structure can be enhanced, which is of great help to the expansion performance of the silicon-carbon material.
[0104] In an optional embodiment, the porous carbon modification comprises at least one of the following features (1) to (7):
[0105] (1) The porous carbon is selected from one or more of biomass-based, resin-based, asphalt-based, and petroleum-based;
[0106] (2) Preparation of carbon quantum dot solution, specifically including:
[0107] Mixing raw material A, raw material B and water to obtain a mixed solution, and subjecting the mixed solution to microwave heating treatment;
[0108] (3) Raw material A includes but is not limited to one or more of citric acid, acetic acid, glucose, sucrose, and lactose;
[0109] Optionally, raw material A is selected from citric acid and glucose;
[0110] Raw material B includes but is not limited to one or more of urea, melamine, and dicyandiamide;
[0111] Optionally, raw material B is selected from urea;
[0112] (4) The mass ratio of raw material A to raw material B is 1:(1-5), and the concentration of raw material B in the mixed solution is 0.5-10.0 mol / L;
[0113] Specifically, the mass ratio of raw material A to raw material B can be 1:1, 1:1.5, 1:2, 1:2.5, 1:3, 1:3.5, 1:4, 1:4.5, 1:5 or any ratio within the above range; optionally, the mass ratio of raw material A to raw material B is 1:(1~1.5).
[0114] Specifically, the concentration of raw material B in the mixed solution can be 0.5mol / L, 1.0mol / L, 1.5mol / L, 2.0mol / L, 2.5mol / L, 3.0mol / L, 3.5mol / L, 4.0mol / L, 4.5mol / L, 5.0mol / L, 6mol / L, 8mol / L, 10mol / L or any value within the above range;
[0115] Optionally, the concentration of raw material B in the mixed solution is 2 to 5 mol / L.
[0116] (5) Microwave heating treatment, power of 200-1000 W, temperature of 60-100° C., time of 5-60 min;
[0117] Specifically, the power can be 200W, 300W, 400W, 500W, 600W, 700W, 800W, 900W, 1000W or any value within the above range; optionally, for microwave heating treatment, the power is 400-800W.
[0118] Specifically, the temperature can be 60°C, 65°C, 70°C, 75°C, 80°C, 85°C, 90°C, 95°C, 100°C or any value within the above range; optionally, the microwave heating treatment is at a temperature of 70-90°C; further optionally, the temperature is 80°C.
[0119] Specifically, the time can be 20 min, 25 min, 30 min, 35 min, 40 min, 45 min, 50 min, 55 min, 60 min or any value within the above range; optionally, the microwave heating treatment time is 20 to 60 min; the specific time is adaptively adjusted in this field according to the adjustment of the heating temperature and power.
[0120] (6) The mass ratio of the total mass of raw material A and raw material B to the porous carbon is (1-5):(1-10); specifically, it can be 1:0.2, 1:0.5, 1:1, 1:2, 1:3, 1:4, 1:5, 1:6, 1:7, 1:8, 1:9, 1:10 or any ratio within the above range.
[0121] The experiment found that as the total mass ratio of raw material A and raw material B to the mass ratio of porous carbon becomes smaller, the carbon quantum dots combined with porous carbon become fewer, the resistance of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material increases, and the pore volume decreases; the rate performance and reversible specific capacity of the assembled battery both decrease slightly; the mass ratio of A and raw material B to porous carbon increases, the carbon quantum dots combined with porous carbon increase, the resistance decreases, the pore volume is larger, and the rate performance and reversible specific capacity of the assembled battery both increase slightly; but if the total mass ratio of raw material A and raw material B to porous carbon is too large, there are too many carbon quantum dots, and more gas is formed by the reaction of carbon quantum dots and substrate, which expands the microporous structure into slightly larger mesopores, causing the deposited silicon to agglomerate, and excessive introduction makes the pore wall too thin, not only the capacity is low but also the stability is greatly reduced.
[0122] Optionally, the mass ratio of the total mass of raw material A and raw material B to the mass of porous carbon is 1:(2-5);
[0123] Further optionally, the mass ratio of the total mass of raw material A and raw material B to the mass of porous carbon is 1:(2-4);
[0124] More optionally, the mass ratio is 1:(2-3).
[0125] (7) Modification treatment, pressure is 2-10 MPa, temperature is 150-200°C;
[0126] Specifically, the pressure can be 2MPa, 2.5MPa, 3MPa, 3.5MPa, 4MPa, 4.5MPa, 5MPa, 5.5MPa, 6MPa, 6.5MPa, 7MPa, 7.5MPa, 8MPa, 8.5MPa, 9MPa, 9.5MPa, 10MPa or any value within the above range.
[0127] Experiments have found that the modification pressure affects the effective and stable combination of carbon quantum dots and porous carbon. If the pressure is too low, the carbon quantum dots can hardly combine effectively with the porous carbon, and cannot improve the conductivity and regulate the pore structure. The electrochemical performance of the assembled battery is equivalent to that of the assembled battery without modifying the porous carbon.
[0128] Optionally, the pressure of the modification treatment is 4 to 8 MPa;
[0129] Further optionally, the pressure of the modification treatment is 6 to 8 MPa.
[0130] In an optional embodiment, the carbon quantum dot solution is prepared by microwave heating and then secondary heating;
[0131] Experiments have shown that secondary heating can further enhance the bonding ability between carbon quantum dots and porous carbon, improve the quality of modified porous carbon, further improve the conductivity of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material, and the electrochemical properties of the final assembled battery, including rate performance and cycle stability.
[0132] Optionally, the secondary heating temperature is 60-80°C; specifically, it can be 60°C, 65°C, 70°C, 75°C, 80°C or any value within the above range.
[0133] Optionally, the secondary heating time is 1 to 5 h; specifically, it can be 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4 h, 4.5 h, 5 h or any value within the above range.
[0134] In an optional embodiment, the crude product after microwave treatment, or microwave and secondary heating treatment, needs to be centrifuged multiple times until no sediment appears, and the centrifuged solution is collected as the carbon quantum dot solution;
[0135] Optionally, the centrifugal treatment has a rotation speed of 1500-3000 r / min; specifically, it can be 1500 r / min, 1600 r / min, 1700 r / min, 1800 r / min, 1900 r / min, 2000 r / min, 2100 r / min, 2200 r / min, 2300 r / min, 2400 r / min, 2500 r / min, 2600 r / min, 2700 r / min, 2800 r / min, 2900 r / min, 3000 r / min or any value within the above range.
[0136] In an alternative embodiment, the silicon deposition:
[0137] The raw material gas used includes silicon source gas;
[0138] Optionally, the silicon source gas includes but is not limited to common types such as silane and silicon tetrachloride.
[0139] The flow rate of the silicon source gas is 1 to 15 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min or any value within the above range.
[0140] The silicon deposition temperature is 400-580°C; specifically, it can be 400°C, 420°C, 440°C, 460°C, 480°C, 500°C, 520°C, 540°C, 560°C, 580°C or any value within the above range; optionally, the silicon deposition temperature is 420-520°C.
[0141] Optionally, the silicon deposition is carried out in a rotary kiln; further optionally, the rotation speed of the rotary kiln is 0.1-2.5 r / min; specifically, it can be 0.1 r / min, 0.5 r / min, 1.0 r / min, 1.5 r / min, 2.0 r / min, 2.5 r / min or any value within the above range.
[0142] The silicon deposition time is 2 to 20 hours; specifically, it can be 2 hours, 5 hours, 8 hours, 10 hours, 12 hours, 15 hours, 18 hours, 20 hours or any value within the above range.
[0143] In an optional embodiment, the carbon coating process:
[0144] The raw gas used includes carbon-containing gas;
[0145] Optionally, the carbon-containing gas is selected from at least one of C1-4 alkanes, such as methane, ethane, propane, butane, C2-4 olefins, such as ethylene, propylene, butene, 1,3-butadiene, and C2-4 alkynes, such as acetylene, propyne, and butyne;
[0146] The flow rate of the carbon-containing gas is 1 to 15 L / min; specifically, it can be 1 L / min, 2 L / min, 3 L / min, 4 L / min, 5 L / min, 6 L / min, 7 L / min, 8 L / min, 9 L / min, 10 L / min, 11 L / min, 12 L / min, 13 L / min, 14 L / min, 15 L / min or any value within the above range.
[0147] Optionally, the carbon coating treatment is also carried out in a rotary kiln; further optionally, the rotation speed of the rotary kiln is 0.1-2.5r / min; specifically, it can be 0.1r / min, 0.5r / min, 1.0r / min, 1.5r / min, 2.0r / min, 2.5r / min or any value within the above range.
[0148] The temperature of the carbon coating treatment is 500-1000°C; specifically, it can be 500°C, 550°C, 600°C, 650°C, 700°C, 750°C, 800°C, 850°C, 900°C, 950°C, 1000°C or any value within the above range; optionally, the temperature of the carbon coating treatment is 550-750°C.
[0149] The carbon coating process is performed under an inert atmosphere.
[0150] In a third aspect, the present invention further provides a negative electrode plate, comprising the above-mentioned carbon quantum dot-modified silicon-carbon negative electrode material.
[0151] In a fourth aspect, the present invention further provides a secondary battery comprising the above-mentioned negative electrode material.
[0152] Example 1
[0153] (1) Preparation of carbon quantum dot solution: 3 kg of citric acid (15.6 mol) and 3 kg of urea (50 mol) were added to 10 kg of distilled water, heated at 80 ° C for 40 min in a microwave reactor (power of 550 W), and then heated at 80 ° C for 3 h in a vacuum drying oven, and then centrifuged at 3000 r / min for multiple times until no sediment appeared, and a total of 7.5 kg of the centrifuged solution was collected, which was the carbon quantum dot solution;
[0154] (2) Porous carbon modification: 18 kg of porous carbon (D 50 =8.1μm, specific surface area is 1820m 2 / g, and the total pore volume is 0.91cm 3 / g, with an average pore size of 5.5 nm) was added to the carbon quantum dot solution prepared in step (1) and mixed evenly, and the material was transferred to a high-pressure reactor, the pressure in the reactor was controlled to be 6 MPa, and carbonized at 180° C. for 15 h, and then the reactant was washed and finally dried at 100° C. to obtain modified porous carbon;
[0155] After testing, the specific surface area of the modified porous carbon is 1980m 2 / g, with a total pore volume of 1.01 cm 3 / g, and the average pore size is 3.2nm.
[0156] (3) Silicon source deposition: 10 kg of the modified porous carbon prepared in step (2) was added to a rotary kiln as a substrate. After evacuation, nitrogen was backfilled to maintain an inert atmosphere in the furnace, and the oxygen content in the furnace was controlled at 40 ppm. Then nitrogen was introduced, and the nitrogen flow rate was maintained at 5 L / min. The temperature was raised to 480° C.; then the nitrogen was cut off, and monosilane gas was introduced. The furnace speed was controlled at 1 r / min, the monosilane gas flow rate was 6 L / min, and the ventilation time was maintained for 16 h to obtain a silicon / carbon material;
[0157] (4) Carbon coating treatment: Based on step (3), nitrogen gas was introduced, the nitrogen flow rate was maintained at 5 L / min, and the temperature was raised to 600°C; then, acetylene gas was introduced, the furnace speed was controlled at 1.5 r / min, the acetylene flow rate was 10 L / min, and the ventilation was continued for 3 h. The acetylene gas was decomposed by high-temperature pyrolysis, and carbon atoms were coated on the porous carbon surface of the deposited silicon, completing the carbon source coating and obtaining a carbon quantum dot-modified silicon-carbon composite negative electrode material.
[0158] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 1.9 nm, and the half-peak width was 4.305.
[0159] Example 2
[0160] The preparation process is substantially the same as that of Example 1, except that in step (1), urea is replaced by an equal mass of melamine (23.8 mol).
[0161] Example 3
[0162] (1) Preparation of carbon quantum dot solution: 2 kg of citric acid and 2.5 kg of melamine (19.8 mol) were added to 7.5 kg of distilled water, heated at 80 ° C for 40 min in a microwave reactor (power 600 W), then heated at 80 ° C for 3 h in a vacuum drying oven, and then centrifuged at 3000 r / min for multiple times until no sediment appeared. A total of 4.8 kg of the centrifuged solution was collected, which was the carbon quantum dot solution;
[0163] (2) Porous carbon modification: 22.5 kg of porous carbon (D 50 =8.1μm, specific surface area is 1820m 2 / g, and the total pore volume is 0.91cm 3 / g, with an average pore size of 5.5 nm) was added to the carbon quantum dot solution prepared in step (1), mixed evenly, and the material was transferred to a high-pressure reactor (6 MPa) and carbonized at 180° C. for 15 h, and then the reactant was washed and then dried at 100° C. to obtain modified porous carbon;
[0164] After testing, the specific surface area of the modified porous carbon prepared in this embodiment is 1855m 2 / g, and the total pore volume is 0.93cm 3 / g, and the average pore size is 4.5nm.
[0165] Steps (3) to (4) are exactly the same as those in Example 1.
[0166] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 3.0 nm, and the half-peak width was 2.734.
[0167] Example 4
[0168] (1) Preparation of carbon quantum dot solution: 3 kg of citric acid and 4 kg of melamine (31.7 mol) were added to 11 kg of distilled water, heated at 80 ° C for 40 min in a microwave reactor (power of 430 W), and then heated at 80 ° C for 3 h in a vacuum drying oven, and then centrifuged at 3000 r / min for multiple times until no sediment appeared, and a total of 8.2 kg of the centrifuged solution was collected, which was the carbon quantum dot solution;
[0169] (2) Porous carbon modification: 15 kg of porous carbon (D 50 =8.1μm, specific surface area is 1820m 2 / g, and the total pore volume is 0.91cm 3 / g, with an average pore size of 5.5 nm) was added to the carbon quantum dot solution prepared in step (1) and mixed evenly, and the material was transferred to a high-pressure (6 MPa) reactor for carbonization at 180° C. for 15 h, and then the reactant was washed and then dried at 100° C. to obtain modified porous carbon;
[0170] After testing, the specific surface area of the modified porous carbon prepared in this embodiment is 2187m 2 / g, with a total pore volume of 1.15 cm 3 / g, and the average pore size is 2.1nm.
[0171] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 1.5 nm, and the half-peak width was 5.314.
[0172] Example 5
[0173] The preparation process is basically the same as that of Example 1, except that in step (2), the pressure of the high-pressure reactor is replaced with 2 MPa.
[0174] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 3.2 nm, and the half-peak width was 2.724.
[0175] Example 6
[0176] The preparation process is basically the same as that of Example 1, except that in step (2), the pressure of the high-pressure reactor is replaced with 4 MPa.
[0177] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 2.49 nm, and the half-peak width was 3.545.
[0178] Example 7
[0179] The preparation process is basically the same as that of Example 1, except that in step (2), the pressure of the high-pressure reactor is replaced with 8 MPa.
[0180] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 1.8 nm, and the half-peak width was 4.411.
[0181] Example 8
[0182] The preparation process is basically the same as that of Example 1, the only difference being that in step (4), the carbon coating temperature is replaced with 900°C.
[0183] Combined with XRD( Figure 1 ), proving that no Si-C bonds are generated in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment, but through XRD test analysis and calculation by the Scherrer formula, it is obtained that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment is 3.5nm, and the half-peak width is 2.523.
[0184] Example 9
[0185] (1) Preparation of carbon quantum dot solution: 3 kg of citric acid and 3 kg of urea were added to 10 kg of distilled water, heated at 80 °C for 40 min in a microwave reactor (power of 550 W), and then centrifuged at 3000 r / min until no sediment appeared, and 7.4 kg of the centrifuged solution was collected as the carbon quantum dot solution;
[0186] Steps (2) to (4) are exactly the same as those in Example 1.
[0187] Through XRD test analysis and calculation using the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this embodiment was 2.9 nm, and the half-peak width was 2.987.
[0188] Comparative Example 1
[0189] (1) Silicon source deposition: 10 kg of porous carbon (D 50 =8.1μm, specific surface area is 1820m 2 / g, and the total pore volume is 0.91cm 3 / g, with an average pore size of 5.5 nm) was added into a rotary kiln as a substrate, and after evacuation, nitrogen was backfilled to maintain an inert atmosphere in the furnace, and the oxygen content in the furnace was controlled at 40 ppm, and then nitrogen was passed through, and the nitrogen flow rate was maintained at 5 L / min, and the temperature was raised to 480°C; then the nitrogen was cut off, and monosilane gas was passed through, and the furnace speed was controlled at 1 r / min, the monosilane gas flow rate was 6 L / min, and the ventilation time was maintained for 16 h to obtain a silicon / carbon material;
[0190] (2) Carbon coating: Based on step (1), nitrogen gas is introduced, the nitrogen flow rate is maintained at 5 L / min, and the temperature is raised to 600°C; then, acetylene gas is introduced, the furnace speed is controlled at 1.5 r / min, the acetylene flow rate is 10 L / min, and the ventilation time is maintained at 3 h. The acetylene gas is decomposed by high-temperature pyrolysis, and carbon atoms are coated on the porous carbon surface of the deposited silicon, completing the carbon source coating and obtaining a carbon quantum dot-modified silicon-carbon composite negative electrode material.
[0191] Through XRD test analysis and calculation based on the Scherrer formula, it was found that the average size of nano-silicon in the silicon-carbon composite negative electrode material prepared in this comparative example was 5 nm, and the half-peak width was 1.639.
[0192] Comparative Example 2
[0193] The preparation process is basically the same as that of Example 1, except that in step (2), the mass of the porous carbon is replaced with 1 kg.
[0194] After testing, the specific surface area of the modified porous carbon prepared in this comparative example is 1503m 2 / g, and the total pore volume is 0.64cm 3 / g, and the average pore size is 6.7nm.
[0195] Through XRD test analysis and calculation based on the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this comparative example was 5.36 nm, and the half-peak width was 1.898.
[0196] Comparative Example 3
[0197] The preparation process is basically the same as that of Example 1, except that in step (2), the pressure of the high-pressure reactor is replaced with 0.5 MPa.
[0198] Through XRD test analysis and calculation based on the Scherrer formula, it was found that the average size of nano-silicon in the carbon quantum dot-modified silicon-carbon composite negative electrode material prepared in this comparative example was 2.60 nm, and the half-peak width was 3.406.
[0199] Comparative Example 4
[0200] The preparation process is basically the same as that of Comparative Example 1, the only difference being that in step (4), the carbon coating temperature is replaced with 900°C.
[0201] Combined with XRD( Figure 1 ), proving that the silicon-carbon composite negative electrode material prepared in this comparative example has silicon-carbon bonds, and the average size of nano-silicon is 7nm, and the half-peak width is 1.267.
[0202] The performance test data of the silicon-carbon composite negative electrode materials prepared in each embodiment and comparative example are listed in the following Table 1, wherein the particle size test is performed by Malvern 3000 test, the powder resistance is measured by a semiconductor powder resistivity tester (30MPa four-probe V1.4), the tap density is measured by a tap density meter, and the specific surface area is tested by Micromeritics 3020.
[0203] Table 1
[0204]
[0205] By comparing Examples 1 and 2 with Comparative Example 1 in Table 1, it can be seen that the conductivity of the silicon-carbon composite negative electrode material modified with carbon quantum dots prepared by urea or melamine is significantly improved, among which the resistance of the silicon-carbon composite negative electrode material modified with carbon quantum dots prepared by urea is lower.
[0206] Comparing Examples 1, 3 to 4 and Comparative Example 2 in Table 1, it can be seen that when the total mass ratio of raw material A and raw material B used to prepare the carbon quantum dot solution to the mass ratio of porous carbon becomes smaller (Example 3), the carbon quantum dots bound to porous carbon become fewer, and the resistance of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material is improved; when the total mass ratio of raw material A and raw material B used to prepare the carbon quantum dot solution to the mass ratio of porous carbon becomes larger (Example 4), the carbon quantum dots bound to porous carbon become more, and the resistance decreases. When the total mass ratio of raw material A and raw material B used to prepare the carbon quantum dot solution to the mass ratio of porous carbon is too large (Comparative Example 2), the specific surface area of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material is significantly increased, which will affect its electrochemical performance.
[0207] By comparing Examples 1, 5 to 7 and Comparative Example 3 in Table 1, it can be seen that when the pressure of porous carbon modification is controlled in the range of 2 to 8 MPa, the conductivity of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material is relatively excellent; when the pressure is controlled at 2 MPa (Example 5), the conductivity of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material is slightly worse than that of the other examples. The reason may be that the pressure is slightly low, and the composite effect of carbon quantum dots and porous carbon is slightly worse. Therefore, it is more preferred to control the pressure at 4 to 8 MPa; when the pressure is too low (Comparative Example 3), the carbon quantum dots can hardly be effectively composited with the porous carbon, and cannot play the role of improving the conductivity, which is similar to the result in Comparative Example 1.
[0208] By comparing Examples 1 and 9 in Table 1, it can be seen that when preparing modified porous carbon, the conventional process is to perform microwave heating only, but in the reaction system disclosed in the present invention, it is found that if a secondary heating process is added after microwave heating, the quality of carbon quantum dots can be further improved, and the conductivity of the prepared carbon quantum dot-modified silicon-carbon composite negative electrode material can be further improved.
[0209] Application Examples
[0210] Batteries were assembled using the products prepared in each embodiment and each comparative example as negative electrode materials.
[0211] (1) Preparation of positive electrode sheets: The positive electrode active material lithium nickel cobalt manganese oxide (NCM811), the conductive agent SuperP, carbon nanotubes, the binder polyvinylidene fluoride (PVDF) and N-methylpyrrolidone (NMP) were mixed in a mass ratio of 97:1:0.5:1.5 to form a positive electrode slurry (solid content of 70 wt%), which was coated on both sides of the current collector aluminum foil, dried at 100°C, and cold pressed at 4 MPa at room temperature, and then trimmed, cut, and slit, and the tabs were welded to form positive electrode sheets.
[0212] (2) Preparation of negative electrode sheets: Under a nitrogen protective atmosphere, the solvent N-methylpyrrolidone (NMP) and the binder PVDF were stirred and mixed, and then the conductive agent SuperP was added and stirred and mixed. Then, the products prepared in each embodiment and each comparative example were added as negative electrode active materials and stirred and mixed thoroughly to prepare a negative electrode slurry (solid content of 50wt%).
[0213] The negative electrode slurry is coated on both sides of the current collector copper foil, dried at 100°C, cold pressed at 4MPa at room temperature, and then trimmed, cut, stripped, and the tabs are welded to make negative electrode sheets.
[0214] (3) Assembly of lithium-ion batteries
[0215] Using PE porous polymer film as separator, the prepared positive electrode sheet, separator and negative electrode sheet are stacked in order, with the separator placed between the positive and negative electrode sheets, and wound to obtain a bare battery cell; the bare battery cell is placed in an aluminum-plastic shell package and placed under a relative vacuum pressure of -0.95×10 5 Pa, dried at 100 ° C to a moisture content of less than 100 ppm. The electrolyte is injected into the dried bare battery, wherein the electrolyte consists of ethylene carbonate (EC), ethyl methyl carbonate (EMC) and diethyl carbonate (DEC) (EC:EMC:DEC volume ratio = 1:1:1) and LiPF6 (1.0M), and is packaged, left to stand, formed (0.02C constant current charging for 2h, 0.1C constant current charging for 2h), shaped, and capacity tested (capacity division) to make a soft-pack liquid lithium-ion battery.
[0216] When assembling the battery, five batteries are prepared for each test, and a total of five sets of data are tested. The final performance is the average value of the five sets of data.
[0217] The battery cycle performance is tested on the Xinwei equipment, specifically:
[0218] At 25°C, first discharge to 0.005V at 0.1C, then discharge to 0.001V at 0.08C, discharge to 0.001V at 0.05C, discharge to 0.001V at 0.02C, and let stand for 10 minutes; then charge to 1.5V at 0.1C, let stand for 10 minutes, record the charge and discharge capacity after the first cycle, and calculate the first coulomb efficiency; cycle 100 times in the above manner, record the charge and discharge capacity after 100 times, calculate the capacity retention rate after 100 cycles, and the test and calculation process of the capacity retention rate after 500 cycles adopt the same method. At the same time, the discharge capacity under different discharge currents is used to test the rate performance of the battery (discharge to 0.005V at 2C, then discharge to 0.001V at 1.6C, discharge to 0.001V at 1C, and discharge to 0.001V at 0.4C). The specific test / calculation results are shown in Table 2 below.
[0219] Table 2
[0220]
[0221] By comparing the examples and comparative examples in Table 2, it can be seen that the battery assembled with the negative electrode material prepared by the present invention has high rate performance, high cycle stability, high capacity and high initial efficiency. With the change of the total mass ratio of raw material A and raw material B for preparing the carbon quantum dot solution and the mass ratio of porous carbon, the change of the pressure of porous carbon modification and the process optimization, the electrochemical performance of the battery assembled with the prepared negative electrode material changes. Among them, Example 1 is the best example.
[0222] By comparing Example 1, Comparative Examples 1 and 4 in Table 2, it can be seen that compared with the comparative example in which the porous carbon is not modified, the electrochemical performance of the battery assembled by the negative electrode material prepared by the specific modification treatment of the carbon quantum dot solution is significantly better than that of the comparative example.
[0223] By comparing Example 1 and Comparative Example 2 in Table 2, it can be seen that when the total mass of raw material A and raw material B used to prepare the carbon quantum dot solution is too large to the mass ratio of the porous carbon, the rate performance of the assembled battery is better, but the cycle stability, initial reversible specific capacity and first efficiency are significantly reduced; analysis shows that the reason may be too many quantum dots, and more gas is formed by the reaction of quantum dots and porous carbon, which expands the microporous structure into slightly larger mesopores, causing the deposited silicon to agglomerate, and excessive introduction makes the pore wall too thin, not only the capacity is low but also the stability is greatly reduced.
[0224] By comparing Example 1 and Comparative Example 3 in Table 2, it can be seen that when the pressure of porous carbon modification is too low, the electrochemical performance of the battery assembled with the negative electrode material is equivalent to that of the battery assembled without modifying the porous carbon.
[0225] The above-mentioned embodiments are preferred embodiments, but the protection scope of the present invention is not limited thereto. A person skilled in the art can easily understand the spirit of the present invention based on the above-mentioned embodiments and make different extensions and changes. However, as long as they do not deviate from the spirit of the present invention, they are all within the protection scope of the present invention.
Claims
1. A carbon quantum dot-modified silicon-carbon negative electrode material, characterized in that: It comprises a modified porous carbon substrate, nano-silicon deposited in the modified porous carbon substrate, and a carbon layer uniformly coated on the modified porous carbon substrate and / or the nano-silicon; According to XRD testing, the half-peak width of the nano-silicon is not less than 2.
5.
2. The carbon quantum dot-modified silicon-carbon negative electrode material according to claim 1, characterized in that: The modified porous carbon substrate satisfies at least one of the following A to D: A. Modification of porous carbon substrate D 50 =5~12μm; B. The specific surface area of the modified porous carbon substrate is 1600-2400 m 2 / g; C. The total pore volume of the modified porous carbon substrate is 0.70-1.20 cm 3 / g; D. The average pore size of the modified porous carbon substrate is 1 to 5 nm.
3. The carbon quantum dot-modified silicon-carbon negative electrode material according to claim 1, characterized in that: The modified porous carbon substrate is obtained by uniformly mixing porous carbon and a carbon quantum dot solution and then subjecting the mixture to a modification treatment.
4. The carbon quantum dot-modified silicon-carbon negative electrode material according to claim 1, characterized in that: The carbon quantum dot-modified silicon-carbon negative electrode material satisfies at least one of the following A to F: AD 50 8±1μm; B. Tap density is 0.9±0.1g / cm 3 ; C. Resistivity is 1~5Ω·cm; D. Specific surface area is 1 to 3 m 2 / g; E. The mass percentage of the carbon layer is 1 to 5 wt%; F. The average size of nano-silicon is no more than 3.5nm.
5. A carbon quantum dot-modified silicon-carbon negative electrode material according to any one of claims 1 to 4, characterized in that: include: Porous carbon modification, mixing the porous carbon and the carbon quantum dot solution evenly, transferring the mixture into a high-pressure reactor for modification treatment, and obtaining modified porous carbon; Silicon deposition, placing the modified porous carbon as a substrate in a raw gas environment containing a silicon source gas, and performing vapor deposition to obtain a porous carbon substrate loaded with nano-silicon particles; Carbon coating treatment is performed by placing a porous carbon substrate loaded with nano-silicon particles in a raw gas environment containing a carbon source gas, and performing vapor deposition to obtain a silicon-carbon negative electrode material modified with carbon quantum dots.
6. The carbon quantum dot-modified silicon-carbon negative electrode material according to claim 5, characterized in that: The porous carbon modification comprises at least one of the following features (1) to (7): (1) The porous carbon is selected from one or more of biomass-based, resin-based, asphalt-based, and petroleum-based; (2) Preparation of carbon quantum dot solution, specifically including: Mixing raw material A, raw material B and water to obtain a mixed solution, and subjecting the mixed solution to microwave heating treatment; (3) Raw material A includes but is not limited to one or more of citric acid, acetic acid, glucose, sucrose, and lactose; Raw material B includes but is not limited to one or more of urea, melamine, and dicyandiamide; (4) The mass ratio of raw material A to raw material B is 1:(1-5), and the concentration of raw material B in the mixed solution is 0.5-10.0 mol / L; (5) Microwave heating treatment, power of 200-1000 W, temperature of 60-100° C., time of 5-60 min; (6) The mass ratio of the total mass of raw material A and raw material B to the mass of porous carbon is (1-5):(1-10); (7) Modification treatment: pressure is 2-10 MPa and temperature is 150-200°C.
7. The carbon quantum dot-modified silicon-carbon negative electrode material according to claim 6, characterized in that: The carbon quantum dot solution is prepared by microwave heating and then secondary heating; The secondary heating is performed at a temperature of 60 to 80° C. for 1 to 5 hours.
8. The carbon quantum dot-modified silicon-carbon negative electrode material according to claim 5, characterized in that: The silicon deposition: The raw material gas used includes silicon source gas; The flow rate of the silicon source gas is 1 to 15 L / min; The silicon deposition temperature is 400-580°C; The silicon deposition time is 2 to 20 hours; The carbon coating treatment: The raw gas used includes carbon-containing gas; The flow rate of the carbon-containing gas is 1 to 15 L / min; The carbon coating treatment is performed at a temperature of 500 to 1000°C; The carbon coating process is performed under an inert atmosphere.
9. A negative electrode plate, characterized in that: It comprises the silicon-carbon negative electrode material modified by carbon quantum dots as described in any one of claims 1 to 4.
10. A secondary battery, characterized in that: Comprising the negative electrode sheet as claimed in claim 9.
Citation Information
Cited By
Silicon-carbon negative electrode material, preparation method and application thereof, and battery negative electrode
CN120933333A